'Pesky gNATs': investigating the feasibility of a novel computerized CBT intervention for adolescents with anxiety and/or depression in a Tier 3 CAMHS setting. (1st December 2016) - Chapman, Rosanna; Loades, Maria; O'Reilly, Gary; Coyle, David; Patterson, Mags; Salkovskis, Paul
Abstract: Increasingly, evidence suggests that computerized Cognitive Behavioural Therapy (cCBT) is effective at reducing adolescent anxiety and depression for young people in the general population or those 'at risk'. However, less is known about the acceptability, feasibility and effectiveness of cCBT for adolescents with clinically significant levels of impairment. This study aimed to investigate the feasibility of using a novel cCBT intervention, 'Pesky gNATs', with adolescents aged between 13–18 years with anxiety and/or depression who met the criteria for specialist mental health services. Eleven participants were recruited from a Tier 3 child and adolescent mental health service (CAMHS). Recruitment, attendance and retention rates were recorded and qualitative feedback about the benefits and disadvantages of completing cCBT were obtained during the final session. In addition, a number of outcome measures were completed pre- and post- intervention to assess reliable and clinically significant change. The intervention was very brief comprising of just seven sessions. Participants showed high recruitment and retention rates. All participants who started the intervention completed it. All described the programme as useful and the majority identified several benefits. Four of 11 participants demonstrated reliable reductions in symptoms of depression and anxiety and six of 11 showed decreases in parent-reported symptoms of anxiety and depression following the seven-session intervention. This study demonstrates the acceptability and feasibility of using cCBT in a Tier 3 CAMHS setting. Further research is required to investigate the effect of Pesky gNATs on anxiety and depression in other Tier 3 settings.